'Shades of Grey': The Ethics of Social Work Practice in Relation to Un-prescribed Anabolic Androgenic Steroid Use. Issue 4 (8th August 2019) - Harvey, Orlanda
Abstract : This paper reflects on some of the ethical dilemmas that social workers face when assessing risk in relation to those using substances. It explores how legislation and societal factors can impact not just on people's choices and decisions but also on their 'vulnerability' and access to services. Vulnerability, a contested term, is linked, in this paper, to assessment of risk. There are ethical issues that arise when assessing risk with people who use Anabolic Androgenic Steroids (AAS) from both service user and professional perspectives. These ethical issues concern a person's right to choose and make potentially harmful decisions. The paper argues that using substances such as AAS in and of itself does not suffice to make a person vulnerable but this does not mean that people using AAS are not in need of support. It suggests that there may be some groups of people who are more at risk to starting AAS use and that social workers should be aware of these. It also recommends the need for further qualitative research to understand the reasons for starting use and support to help people stop using AAS.